The Effect of Supplementary Feeding on Blood Pressure and Uric Acid in the Elderly in the Working Area of the Teppo Health Center, Pinrang Regency - Suriani, Suriani; Andi Nurlinda; Patimah, Sitti (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2022)
Background:Hypertension is estimated to be the cause of death for around 7.1 million people worldwide. Aim: The purpose of this study was to analyze differences in blood pressure in the elderly before and after supplementary feeding (SF), to analyze differences in uric acid levels in the elderly before and after giving SF, to analyze the effect of SF on blood pressure in the elderly, to analyze the effect of giving SF to uric acid levels in the elderly. Method:This study uses a Quasi-Experimental method with a Two Group Pretest – Posttest design. The sample consisted of 30 experimental groups and 30 control groups. The results showed that in the intervention group the average pre-test systolic blood pressure was 165.33, SD 14.077, and post-test 141.67 SD 11.472. Meanwhile, in the control group, the average systolic blood pressure before SF was 158.33, SD was 7,466, while in the posttest, it was 158.33, SD was 9,499. Results:In the examination of women's uric acid levels, the pretest showed that the intervention group had an average uric acid level of the elderly before SF which was 6.936, and SD was 0.411. The significance value is 0.000 0.05 meaning that there is an effect, while the post-test is 6359, SD is 0.418. While in the control group the average uric acid level of the elderly before supplementary feeding was 6688, SD 0.298, while in the post-test it was 6759, SD 0.355. The significance value is 0.035 0.05, which means that there is no effect. In men, the pretest of the intervention group showed the average uric acid level of the elderly before SF was 7.225, SD was 0.433, while in the posttest it was 6550, SD was 0.578. Meanwhile, in the control group, the average uric acid level before supplementary feeding was 7.215, SD 0.443. Conclusions:There are differences in blood pressure and uric acid in the elderly before and after SF and there is a significant effect of giving SF on blood pressure and uric acid in the elderly.